Knowledge, Attitude and Practice Towards COVID-19 Among People in Adiyaman, Turkey - Dündar, Emel; Kaya, Ferit; Pirincci, Edibe (My University, 2021)
Aim: This study was conducted to examine the knowledge, attitude and practices of individuals aged 18 and over towards one of the coronavirus outbreak COVID-19. Material and Method: This cross-sectional study was carried out by applying a questionnaire to individuals who were registered toa family medicine unit in Adiyaman between 12 May and 10 July. The study population consists of 1842 people registered in the family physician unit. With 95% confidence interval, 50% prevalence, 0.5 margin of error, the number of people to be sampled was calculated as 255. The questionnaire was applied through face to face interviews. Averages were given with standard deviations. ?² and t test were used as statistical analysis method. The p<0.05 was considered significant. Results: The average age of participants included in the study was 39.92±13.52 years and 63.0% were women. 84.3% were married. The mean knowledge score of the participants was found to be 5.68±1.71. In our study, the mean knowledge score was significantly higher in men, employees, and those with an associate degree or above (p<0.05). The average attitude score of the participants was 2.40±0.78, and mean practice score was 12.17±1.17. The most known symptom in information questions was fever. If vaccination is available, 84.7% wanted to get vaccinated. Conclusion: The mean score of knowledge, attitude and practice of individuals about COVID-19 was lower than expected. The mean score and attitude mean score were significantly higher in men. Therefore training programs should be planned to increase the knowledge level, positive attitudes and good practices of individuals in the struggle against COVID-19.
Keywords: Halk ve Çevre Sağlığı; Sağlık Politikaları ve Hizmetleri